2015
DOI: 10.1001/jama.2015.0956
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Benign Thyroid Nodules

Abstract: Among patients with asymptomatic, sonographically or cytologically benign thyroid nodules, the majority of nodules exhibited no significant size increase during 5 years of follow-up and thyroid cancer was rare. These findings support consideration of revision of current guideline recommendations for follow-up of asymptomatic thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
234
4
16

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(279 citation statements)
references
References 31 publications
14
234
4
16
Order By: Relevance
“…At our institution the malignancy rate among nodules with documented growth is quite low (i.e. 1-2%), in agreement with other papers reporting thyroid lesions followed-up after an initial benign assessment [21][22][23][24]. Finally, in our series PTC/ FTC ratio was 72:1 (216/3 cases).…”
Section: Discussionsupporting
confidence: 91%
“…At our institution the malignancy rate among nodules with documented growth is quite low (i.e. 1-2%), in agreement with other papers reporting thyroid lesions followed-up after an initial benign assessment [21][22][23][24]. Finally, in our series PTC/ FTC ratio was 72:1 (216/3 cases).…”
Section: Discussionsupporting
confidence: 91%
“…This creates an important clinical dilemma as thyroid nodules are very common in 50-67% of the population, and more than 90% are benign (Mazzaferri 1992, Hegedus 2004, Popoveniuc & Jonklaas 2012, Durante et al 2015. Detection rates of thyroid nodules are increasing due to widespread use of imaging modalities in advanced health care systems (Cramer et al 2010, Popoveniuc & Jonklaas 2012.…”
Section: :11mentioning
confidence: 99%
“…Durante et al reported that 15.4% (n=153) of the benign nodules grew using the ATA criteria (9). Only two malignancies were detected from these nodules after second TFNAB.…”
Section: Discussionmentioning
confidence: 99%